GAMBARAN KECEMASAN ATLET MAHASISWA: STUDI PADA UNIT KEGIATAN MAHASISWA (UKM) OLAH RAGA UNIVERSITAS ISLAM MAULANA MALIK IBRAHIM MALANG - Lalu Gigir Gilas Pristiwa; Fathul Lubabin Nuqul (Jurnal Psikologi Integratif, 2018)
Abstract. Fighting anxiety often occurs in male and female athletes, as well as individual group sports and sports. The anxiety is a feeling of worry, anxiety, and uneasiness by considering the game as something dangerous. There are many factors that can cause an athlete to experience anxiety during a match that is dysfunctional thoughts and stress, academic problems, anxiety injuries, and poor team relationships. Other factors also exist from such individuals and the environment, such as negative thoughts on the outcome of the game, the pressure of the coach or supporters. Therefore, the fighting anxiety is very important to be known by every athlete or team that will compete, in order to be able to improve its best performance in the face of the game. This study used a quantitative approach measured using the scale of The Sport Interference Checklist (SIC) to measure athlete's anxiety. The subjects of the study were 110 people consisting of athletes of students in the Sports  student Unit State Islamic University Maulana Malik Ibrahim Malang. With male gender of 64 people and 46 women, as well as individual sports from two sports that is badminton and table tennis totaling 31 people and sports groups from four sports that is soccer, volleyball, basketball, and sepak takraw amounted to 79 person. The analysis is descriptive analysis. The results showed that there was no difference between sex of male athlete with percentage 63,00% and woman equal to 66,89%, because anxiety at athlete evaluated from gender have no significance, and difference between type of individual sport with percentage 67, 12% and sports groups of 63.64%, if reviewed the anxiety of the athlete's sports type does not have significant. This means that athletes in the Sport students Unit equally have anxiety problems when playing.